PESAN KOMUNIKASI DI BALIK SENI TARI CACI MANGGARAI RAYA, PROVINSI NTT (Studi Kasus Permainan Caci Ikatan Keluarga Satar Mese dan Lamba Leda, di Kota Kupang) (Verba Vitae Unwira, 2020)
Communication Messages Behind Caci Dance of Manggarai Raya, of East Nusa Tenggara Province(A case Study on Caci Dance Performed by Satar Mese Community and Lamba Leda Community in Kupang City)To people of Manggarai Raya, Caci contains meaningful symbols. However, there are still many people, mainly the young, who are not aware of the existence of those symbols. This study aims to (1) describe the phenomenon of social behavior expressed in Caci Dancing performed by the Dacing group of Lamba Leda and of the Satar Mese of Manggarai Raya in Kupang City, (2) identify messages communicated in the Caci Dancing performed by the groups, (3) offer ways to promote Caci in order to maintain its existence. This is a descriptive-qualitative study presented in a systematic way. The study found that, (1) Caci is a cultural ritual of Manggarai people that involve elements such as human being as creatures of culture, rituals, and materials (e.g. clothes and others). Those elements present symbols containing historical, social, and cultural values of Manggarai people. (2) Caci contains positive values such as being supportive, togetherness, kinship, fraternity, and collaboration. (3) Understanding of those values takes a long process. It should become a habit. The young people are encouraged to maintain and promote those values by actively participate in Caci performances as this may become a medium of education for them.
Keywords: Caci; Dance; Performance; Games; Cultural Tourism Objects